Sirolimus Reduces the Incidence and Progression of UVB-Induced Skin Cancer in SKH Mice even with Co-administration of Cyclosporine A - Wulff, Brian C. (2008)
Transplant immunosuppressants have been implicated in the increased incidence of non-melanoma skin cancer in transplant recipients, most of whom harbor considerable UVB-induced DNA damage in their skin prior to transplantation. This study was designed to evaluate the effects of two commonly used immunosuppressive drugs, cyclosporine A (CsA) and sirolimus (SRL), on the development and progression of UVB-induced non-melanoma skin cancer. SKH-1 hairless mice were exposed to UVB alone for 15 weeks, and then were treated with CsA, SRL, or CsA+SRL for 9 weeks following cessation of UVB treatment. Compared with vehicle, CsA treatment resulted in enhanced tumor size and progression. In contrast, mice treated with SRL or CsA+SRL had decreased tumor multiplicity, size, and progression compared with vehicle-treated mice. CsA, but not SRL or combined treatment, increased dermal mast cell numbers and TGF-β1 levels in the skin. These findings demonstrate that specific immunosuppressive agents differentially alter the cutaneous tumor microenvironment, which in turn may contribute to enhanced development of UVB-induced skin cancer in transplant recipients. Furthermore, these results suggest that CsA alone causes enhanced growth and progression of skin cancer, whereas co-administration of SRL with CsA causes the opposite effect.